Flexible growing rods: a biomechanical pilot study of polymer rod constructs in the stability of skeletally immature spines. Issue 1 (December 2016) - Bylski-Austrow, Donita; Glos, David; Bonifas, Anne; Carvalho, Max; Coombs, Matthew; Sturm, Peter
Abstract Background Surgical treatments for early onset scoliosis (EOS) correct curvatures and improve respiratory function but involve many complications. A distractible, or 'growing rod, ' implant construct that is more flexible than current metal rod systems may sufficiently correct curves in small children and reduce complications due to biomechanical factors. The purpose of this pilot study was to determine ranges of motion (ROM) after implantation of simulated growing rod constructs with a range of clinically relevant structural properties. The hypothesis was that ROM of spines instrumented with polymer rods would be greater than conventional metal rods and lower than non-instrumented controls. Methods Biomechanical tests were conducted on six thoracic spines from skeletally immature domestic swines (35–40 kg). Paired pedicle screws were used as anchors at proximal and distal levels. Specimens were tested under the following conditions: control, then dual rods of polyetheretherketone (PEEK) (diameter 6.25 mm), titanium (4 mm), and cobalt-chrome alloy (CoCr) (5 mm). Lateral bending (LB) and flexion-extension (FE) moments were applied, and vertebral rotations were measured. Differences were determined by two-tailed t-tests and Bonferroni for four primary comparisons: PEEK vs control and PEEK vs CoCr, in LB and FE (α = 0.05/4). Results In LB, ROM of spine segments after instrumenting with PEEK rods was lower than the non-instrumented control condition at each instrumented level. ROM was greater with PEEK rods than with Ti and CoCr rods at every instrumented level. Combining treated levels, in LB, ROM for PEEK rods was 35 % of control (p  < 0.0001) and 270 % of CoCr rods (p  < 0.01). In FE, ROM with PEEK was 27 % of control (p  < 0.001) and 180 % of CoCr (p  < 0.01). At proximal and distal adjacent non-instrumented levels in FE, mean ROM was lower for PEEK than for either metal. Conclusions PEEK rods increased flexibility versus metal rods, and decreased flexibility versus non-instrumented controls, both over the entire instrumented segment and at each individual level. Smaller mean increases in ROM at proximal and distal adjacent motion segments occurred with PEEK compared to metal rods, which may help decrease complications, such as junctional kyphosis. Flexible growing rods may eventually help improve treatment options for young patients with severe deformity.